PEMANFAATAN Azolla pinnata R. Br DALAM PENYERAPAN Zn DARI LIMBAH CAIR PABRIK KARET SEBAGAI FITOREMEDIATOR - Arimby, Citra; Lestari, Wahyu; Azis, Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Large rubber plantations in Riau Province create rubber factories, that potentially produce liquid waste contain Zn above the environment quality standard, that may cause water pollution. Efforts to overcome pollution caused by the waste can be done by phytoremediation using Azolla pinnata. The purpose of this research was to test the effect of rubber factory liquid waste on the growth of A. pinnata. The research used Complete Random Design with dilution of waste treatments 25, 50, 75 and without dillution (100%), and no waste treatment as a control. A. pinnata was grown in each treatment for 12 days. Data was analyzed using ANOVA and tested further with LSD at 5% level. The results showed that the fresh weight of A. pinnata in the waste without dilution increased up to 60.87 g with the highest relative growth was found in 9th day in two treatments (75% dilution and without dilution).